Organization of detection and investigation of deliberate infliction of moderate harm to health by the inquiry units of the internal affairs bodies - A.V. Yashin (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2022)
Background. The commission of crimes related to the deliberate infliction of moderate harm to health in modern Russia is a fairly widespread socially dangerous phe-nomenon. In turn, the legal norms regulating criminal liability for such acts act as a means of preventing other grave and especially grave crimes against the individual. However, an analysis of the scientific literature shows that very little attention is paid to the problems of identifying and organizing the investigation of intentional infliction of moderate harm to health, which confirms the relevance of the content of this article. The purpose of the work is to propose the most effective directions for the investigators of the internal affairs bodies to identify and investigate the crimes in question. Materials and methods. The article used normative legal acts and scientific works on the problem under study, official statistical information on crimes associated with the deliberate infliction of moderate harm to health, materials of judicial practice. The methodological basis was the universal dialectical me-thod of cognition. Also, during the preparation of the article, the following methods were implemented: logical, formal-legal, statistical, the study of judicial practice. Results. The ana-lysis of the official statistical indicators on the crimes under consideration is carried out, the features of the identification and organization of acts associated with the deliberate inflic-tion of moderate harm to health are studied. Conclusions. Based on the results obtained, proposals were made aimed at increasing the efficiency of the investigation units of the internal affairs bodies in the area under consideration.